β-1,4-Xylan backbone synthesis in higher plants: How complex can it be? - Anders, Nadine; Wilson, Louis Frederick Lundy; Sorieul, Mathias; Nikolovski, Nino; Dupree, Paul (Frontiers in Plant Science, 2023)
Xylan is a hemicellulose present in the cell walls of all land plants. Glycosyltransferases of the GT43 (IRX9/IRX9L and IRX14/IRX14L) and GT47 (IRX10/IRX10L) families are involved in the biosynthesis of its β-(1,4)-linked xylose backbone, which can be further modified by acetylation and sugar side chains. However, it remains unclear how the different enzymes work together to synthesise the xylan backbone. A xylan synthesis complex (XSC) has been described in the monocots wheat and asparagus, and co-expression of asparagus AoIRX9, AoIRX10 and AoIRX14A is required to form a catalytically active complex for secondary cell wall xylan biosynthesis. Here, we argue that an equivalent XSC exists for the synthesis of the primary cell wall of the eudicot Arabidopsis thaliana, consisting of IRX9L, IRX10L and IRX14. This would suggest the existence of distinct XSCs for primary and secondary cell wall xylan synthesis, reminiscent of the distinct cellulose synthesis complexes (CSCs) of the primary and secondary cell wall. In contrast to the CSC, in which each CESA protein has catalytic activity, the XSC seems to contain proteins with non-catalytic function with each component bearing potentially unique but crucial roles. Moreover, the core XSC formed by a combination of IRX9/IRX9L, IRX10/IRX10L and IRX14/IRX14L might not be stable in its composition during transit from the endoplasmic reticulum to the Golgi apparatus. Instead, potential dynamic changes of the XSC might be a means of regulating xylan biosynthesis to facilitate coordinated deposition of tailored polysaccharides in the plant cell wall.